#### Answer

{-19}

#### Work Step by Step

13x + 14 = -5 + 12x
Step 1 : Collect variable terms on one side and constants on the other side.
subtract 12x from both the sides
13x + 14 - 12x = -5 +12x -12x
Simplify
x + 14 = -5
Subtract -14 from both the sides
x + 14 -14 = -5 -14
Simplify
x = -19
Now we check the proposed solution,-19 , by replacing x with -19 in the original equation.
Step 1: the original equation 13x + 14 = -5 + 12x
Step2: Substitute -19 for x
13(-19) + 14 = -5 + 12(-19)
Step 3: Multiply 13(-19) = 13 .-19 = -247, 12(-19) = 12. -19 = -228
-247 + 14= -228 - 5
Step 4: Solve
-233 = -233
Since the check results in true statement, we conclude that the solution set of the given equation is {-19}